Chemical contaminants in Brazilian drinking water: a systematic review - Luciano Barros Zini; Mariliz Gutterres (IWA Publishing, 2021)
The goals of this research are to evaluate which chemical contaminations were detected in Brazil's drinking water reported in papers published from 2012 to 2019, to propose guideline values for emerging contaminants and assess which are the priority parameters from a health risk perspective. The methodology used was a systematic review. The chemical contaminants quantified were evaluated according to Brazilian drinking-water standards, and Guideline Values were proposed for emerging pollutants using conservative endpoints from NOAEL and LOAEL available in literature. From 1351 articles evaluated, 15 reached the research goal. Seventy-seven parameters were quantified in Brazilian drinking water from underground, surface and rainwater sources. Soil composition, mining, sewage and agricultural activities were the main sources for the seven classes framed: pesticides, metals, organic, endocrine disruptors, drugs, personal care products and illicit drugs. Twenty-two parameters are listed in the current Brazilian drinking water quality standard and 54 are not. Water was not considered appropriate to drink due to cadmium, aluminum, iron, nickel, mercury, atrazine, propionaldehyde, beryllium, acetone and 17 α-ethinyl estradiol (carcinogenic). Measures to reduce chemical contamination in drinking water need to be taken such as the expansion of sewage treatment and upgrading to tertiary treatment, and controlling and reducing the application of pesticides. HIGHLIGHTS 77 parameters were evaluated in Brazilian drinking water from 15/1351 articles.; 10 parameters exceeded the health limits for potability.; Soil components, mining, sewage and agricultural activities were the main sources.; Improve sewage treatment and reduced pesticide use are required.; New guideline values are proposed for 49 emerging pollutants.;